2019
DOI: 10.1373/jalm.2018.027953
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of In Vitro Hemolysis on Measurement of Cell-Free DNA

Abstract: Background Hemolysis during blood drawing is a common cause of laboratory artifacts. Although circulating cell-free tumor DNA and fetal DNA are currently measured in routine practice, the effect of in vitro hemolysis on the measurement of cell-free DNA (cfDNA) has not been investigated. When in vitro hemolysis occurs, cellular DNA could be released from damaged white blood cells and reduce the fraction of circulating tumor DNA and fetal DNA. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…It is well known that WBCs start to lyse over time in the commonly used EDTA tubes, which leads to an elevated DNA background [16,20]. The color of the plasma may be used as a rough standard in some cfDNA testing laboratories to decide whether the sample should be further tested [16,21]. In our study, none of the samples from EDTA tubes, Streck tubes, and ImproGene tubes showed obvious plasma turbidity or darkening on days 0, 3, or 7.…”
Section: Improgene Tubes Control Hemolysis In Blood Samples For 7 Daysmentioning
confidence: 53%
See 1 more Smart Citation
“…It is well known that WBCs start to lyse over time in the commonly used EDTA tubes, which leads to an elevated DNA background [16,20]. The color of the plasma may be used as a rough standard in some cfDNA testing laboratories to decide whether the sample should be further tested [16,21]. In our study, none of the samples from EDTA tubes, Streck tubes, and ImproGene tubes showed obvious plasma turbidity or darkening on days 0, 3, or 7.…”
Section: Improgene Tubes Control Hemolysis In Blood Samples For 7 Daysmentioning
confidence: 53%
“…One of the major technical challenges to use cfDNA as biomarkers is the ability to quantify targets at low concentrations. Any additional DNA released from nucleated cells before the separation of plasma decreases the proportion of fetal or tumor derived cfDNA in the blood [21]. Previous studies have shown that increasing the time interval between the blood draw and the separation of plasma leads to an increase in the total DNA concentration in EDTA tubes [16,18,20].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that later tubes may be preferable for subsequent liquid biopsy analysis. Although we did not specifically investigate the impact of hemolysis on follow-up ctDNA or CTC analysis, previous studies have shown that hemolysis may negatively affect liquid biopsy analysis, leading to lower ctDNA yield or issues with blood coagulation during CTC enrichment (2528). Another interesting finding from our hemolysis analysis was that a switch from non-hemolytic to hemolytic status of the sample (11.6%), and vice versa (5.0%) is a quite frequent phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to the destruction of red blood cells (in vitro hemolysis), white blood cells may also be physically damaged during blood collection. Distinct from erythrocytes, white blood cells contain nuclear DNA, and their lysis during in vitro hemolysis result in cellular DNA being released into the blood [ 37 ].…”
Section: Discussionmentioning
confidence: 99%